(untitled) (Nexo Revista Científica, 2022)
The paper aims to compare the CO2, CO, CH, and O2 concentrations in the exhaust gases of Cummins KTA 50 diesel engines of BelAZ 75131 mining dump trucks equipped with an onboard cryogenic fuel system and running on diesel and gas-diesel fuel at coal mines of Kuzbass (Russia). The research novelty lies in determining ecological efficiency when using liquefied natural gas (methane) as a motor fuel for heavy-duty mining dump trucks. In the near future, the use of this type of motor fuel will minimize the anthropogenic impact on the environment by reducing harmful emissions and provoking the environmental safety of the region where a large amount of mining equipment is used in coal mining enterprises. The demand for mining dump trucks, their operating conditions, and the world experience in converting mining equipment to liquefied natural gas (methane) were briefly analyzed. The use of alternative fuel sources for heavy-duty mining trucks is a promising way to reduce harmful emissions into the atmosphere. This paper presents a research technique. The data on the study of the CO2, CO, and CH groups and O2 concentrations in the exhaust gases of Cummins KTA 50 diesel engines of BelAZ 75131 mining dump trucks hauling rock mass are presented. The obtained data on the CO2, CO, and CH groups and O2 concentrations during diesel and gas-diesel operation of empty and laden BelAZ 75131 mining dump trucks when going uphill and downhill were substantiated. The results of calculating the average weighted emissions of the CO2, CO, and CH groups in the exhaust gases of Cummins KTA 50 diesel engines were presented.